Novel risk patterns of vasovagal reactions in NZ blood donations complicated by COVID-19 restrictions - Wei, Wen-Hua; Smith, Meredith; Vera, Amber; Meads, Kelly; Hessell, Jillayne; Reid, Laura; Scott, Lisa; Burge, Asuka; Kirwan, Susy; Charlewood, Richard; Sadani, Deepak; Walkden, Deborah; et al. (Frontiers in Public Health, 2023)
Introduction. Vasovagal reactions (VVRs) are common but complex donor adverse reactions (DAEs) in blood donations. VVRs have been extensively studied with a multitude of risk factors identified including young age, female gender and first-time donor status. How they may interplay remains obscure. Methods. A total of 1,984,116 blood donations and 27,952 immediate VVRs (iVVRs) and 1365 delayed VVRs (dVVRs) reported between 2011 and 2021 in NZ were used in multivariate logistic regression analyses each concerning donations with iVVRs as cases and those free of DAEs as controls. For each analysis stepwise selection was used to identify the best model and risk factors carrying significant main effects and/or interactions. Identified interactions informed further in-depth regression analyses to dissect iVVR risk patterns. Results. Over 95% of VVRs were iVVRs that had lower female preponderance and deferrals than dVVRs. iVVRs had a school seasonal pattern in whole blood donations driven by first-time donors from schools/colleges, and interactions between gender and age group differentiating the first-time from repeat donations. Subsequent regression analyses identified the known and novel risk factors of year and mobile collection sites and their interactions. iVVR rates were roundly elevated in 2020 and 2021 probably because of Covid-19 restrictions like facemask wearing. Exclusion of the 2020 and 2021 data removed the interactions with year, but confirmed interactions of gender with mobile collection sites (p = 6.2e-07) in first-time donations only and with age group in repeat donations only (p < 2.2e-16), together indicating young female donors at the highest risk of iVVRs. Our results also revealed that donation policy changes contributed to the year effects; donors had a lower iVVR risk at mobile sites than well-medicalized donation centers probably because of under-reporting. Conclusion. Modelling statistical interactions is valuable in identifying odds and revealing novel iVVR risk patterns and insights into blood donations.